Cretan tea (Origanum dictamnus L.) as a functional beverage: an investigation on antiglycative and carbonyl trapping activities. Issue 3 (12th February 2018) - Maietta, Mariarosa; Colombo, Raffaella; Corana, Federica; Papetti, Adele
Abstract : Chemical characterization of dittany infusion and its inhibitory effects on AGEs formation at different stages of the glycation reaction were investigated. Abstract : Accumulation of advanced glycation end products (AGEs) in vivo is associated with many chronic disorders such as diabetes, renal failure, aging, and Alzheimer's disease. The aim of this study was to expand the knowledge about the functional properties of Origanum dictamnus L. beverage (Cretan tea) by an investigation about the inhibitory effects on the formation of AGEs and the capacity to trap dicarbonyl compounds. Dittany infusion was characterized for its polyphenolic composition by RP-HPLC-DAD-ESI/MS n and twenty compounds were detected. Its antiglycative property was evaluated by in vitro BSA-sugar (glucose, fructose, and ribose) and BSA-methylglyoxal (MGO) assays, tests for the formation of Amadori products and dicarbonyl compounds, and the direct glyoxal (GO) and MGO trapping capacity. The infusion showed the highest inhibitory effect on the formation of dicarbonyl compounds and AGEs (activity values range from 72–100%) and only a weak effect on the formation of Amadori products, indicating that the antiglycative action occurred primarily during the last two phases of the non-enzymatic glycation reaction. These activities are partially correlated with the antioxidant/antiradical activity, as demonstrated by the scavenger capacity against the ABTS cation and DPPH stable radicals, and the reducing power. The registered high anti-AGE capacity could probably be ascribed to the dittany polyphenolic composition particularly rich in flavone derivatives. These findings support further investigations to study the feasibility of dittany as an antiglycative agent in food or cosmetic preparation.